Evaluation of statistical analyses for the identification of surrogates and indicators using historical plant data from a water reclamation plant - Coomans, Cornelius Johannes (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.